Ion exchange membrane, electrodialyzer, diffusion dialyzer, water electrolysis device, and method for manufacturing ion exchange membrane
By adopting an ion exchange membrane with a core fiber-protecting structure, the problem of poor bonding between the substrate and the ion exchange resin is solved, the durability and mechanical strength of the ion exchange membrane are improved, and the stable operation of the equipment is ensured.
Patent Information
- Application Number
- JP2023119941
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-07-24
- Publication Date
- 2025-02-05
AI Technical Summary
In the prior art, the ion exchange membrane is prone to decrease in ion permeability and mechanical strength due to poor bonding between the substrate and the ion exchange resin during use, and the ion exchange resin peeling problem is prone to occur in the electrolyte equipment.
The substrate with a core fiber-protecting structure is used to improve the binding force between the substrate and the ion exchange resin by using the first and second resins with different crystal structures, and an ion exchange membrane with a core fiber-protecting structure is formed to enhance mechanical strength and maintain ion permeability.
It improves the durability and mechanical strength of the ion exchange membrane, reduces the peeling phenomenon of ion exchange resin during use, and ensures the stable operation of the equipment.
Smart Images

Figure 2025017064000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an ion exchange membrane, an electrodialysis apparatus, a diffusion dialysis apparatus, a water electrolysis apparatus, and a method for producing an ion exchange membrane. [Background technology]
[0002] Ion exchange membranes include cation exchange membranes that selectively allow cations to pass through and anion exchange membranes that selectively allow anions to pass through. Ion exchange membranes are used in electrodialysis, diffusion dialysis, water electrolysis, and the like. The paste method is known as an industrial method for producing ion exchange membranes. In the paste method, a polymerizable composition containing a monomer capable of introducing an ion exchange group is filled into a substrate, the resulting membrane is polymerized, and then an ion exchange group is introduced to produce an ion exchange membrane. As the substrate, for example, a woven fabric of polyvinyl chloride resin fiber or a porous membrane of polyolefin resin is used. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2023 / 038133 [Patent Document 2] JP 2008-231458 A Summary of the Invention [Problem to be solved by the invention]
[0004] The present invention provides an ion exchange membrane having excellent durability and a method for producing the same, as well as an electrodialysis device, a diffusion dialysis device, and a water electrolysis device each using the ion exchange membrane. [Means for solving the problem]
[0005] According to an embodiment, an ion exchange membrane is provided. The ion exchange membrane includes a substrate and an ion exchange resin supported on the substrate. The substrate includes a core-sheath fiber. The core-sheath fiber includes a core portion including a first resin and a sheath portion that covers the periphery of the core portion and includes a second resin. The second resin has a lower crystallinity than the first resin.
[0006] According to an embodiment, an electrodialysis device is provided. The electrodialysis device includes an ion exchange membrane according to an embodiment.
[0007] According to an embodiment, a diffusion dialysis device is provided. The diffusion dialysis device includes an ion exchange membrane according to an embodiment.
[0008] According to an embodiment, a water electrolysis device is provided. The water electrolysis device includes an ion exchange membrane according to an embodiment.
[0009] According to an embodiment, a method for producing an ion exchange membrane according to the embodiment is provided, which includes filling a substrate with a polymerizable composition for forming an ion exchange resin to obtain a first composite membrane, polymerizing the first composite membrane to obtain a second composite membrane, and introducing an ion exchange group into the second composite membrane to obtain an ion exchange membrane. Effect of the Invention
[0010] The present invention provides an ion exchange membrane having excellent durability and a method for producing the same, as well as an electrodialysis device, a diffusion dialysis device, and a water electrolysis device that use the ion exchange membrane. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a cross-sectional view illustrating an example of an ion exchange membrane according to an embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The ion exchange membrane according to the embodiment includes a substrate and an ion exchange resin supported on the substrate. The substrate includes a core-sheath fiber. The core-sheath fiber includes a core portion including a first resin and a sheath portion that covers the periphery of the core portion and includes a second resin. The second resin has a lower crystallinity than the first resin. The ion exchange membrane according to the embodiment has excellent durability. The present inventors believe that the reason for this is as follows.
[0013] First, in order to realize an ion exchange membrane with excellent durability, the adhesion between the substrate and the ion exchange resin is important. The areas where the substrate and the ion exchange resin are not in close contact become permeation paths for ions and water, which may reduce the ion selective permeability and concentration characteristics of the ion exchange membrane. In addition, the ion exchange resin may peel off during handling, or in the process of forming poorly soluble salts of metal ions and alkalis inside the ion exchange membrane, scale may accumulate in the gap between the substrate and the ion exchange resin, causing the ion exchange resin to fall off from the substrate. In addition, in environments where the solution concentration changes in the stack of an electrodialysis device or the volume of the ion exchange resin is likely to change due to water washing, the ion exchange resin may peel off from the substrate or its performance may decrease due to repeated swelling and shrinkage.
[0014] In order to increase the adhesion between the substrate and the ion exchange resin and to have practical mechanical strength, it has been found that it is important that the monomer for forming the ion exchange resin and the substrate have a moderate affinity, and while the monomer molecules diffuse into the substrate, the substrate swells with the monomer, causing entanglement of the substrate resin, the ion exchange resin, and the polymer chain. That is, if the affinity is too high, the adhesion is increased, but the monomer capable of introducing an ion exchange group diffuses too much into the substrate, so that the mechanical strength of the ion exchange membrane may decrease. On the other hand, if the affinity is too low, the monomer is difficult to diffuse into the substrate, and the adhesion may decrease. Furthermore, by diffusing the monomer capable of introducing an ion exchange group into the substrate, an ion conduction path can be formed inside the substrate, and the resistance can be reduced. In the ion exchange membrane according to the embodiment, a fiber having a core-sheath structure is used as the fiber of the substrate. In this core-sheath fiber, the crystallinity of the second resin constituting the sheath portion is lower than the crystallinity of the first resin constituting the core portion. Therefore, it is considered that the monomer capable of introducing an ion exchange group diffuses relatively easily into the sheath portion and relatively difficult to diffuse into the core portion. Therefore, it is considered that the adhesion is increased in the sheath portion by forming a complex with the ion exchange resin, while the mechanical strength can be maintained in the core portion because the complex with the ion exchange resin is unlikely to occur in the core portion. Therefore, by using this substrate, an ion exchange membrane with excellent adhesion and mechanical strength can be realized.
[0015] [Ion exchange membrane] The ion exchange membrane according to the embodiment includes a substrate and an ion exchange resin supported on the substrate. The ion exchange membrane may be a cation exchange membrane or an anion exchange membrane. The ion exchange membrane according to the embodiment may be used in a hydrogen production device, a water electrolysis device, a fuel cell, an electrodialysis device, a diffusion dialysis device, a pure water production device, an ion-exchanged water production device, etc.
[0016] The substrate may be a woven fabric or a nonwoven fabric. The opening rate of the substrate is, for example, 1% or more and 60% or less. This opening rate can be calculated, for example, by observing the woven fabric from above, measuring the area of the woven fabric part and the area of the void part that is not the woven fabric, and expressing it as a percentage by dividing the area of the void part by the area of the fiber part + the area of the void part.
[0017] The substrate includes a core-sheath fiber. The substrate is preferably a woven fabric consisting of only the core-sheath fiber. The core-sheath fiber may be a multifilament or a monofilament. From the viewpoint of increasing the durability of the ion exchange membrane, the core-sheath fiber is preferably a multifilament.
[0018] The core-sheath fiber includes a core and a sheath that surrounds the core. The core contains a first resin. The core may consist only of the first resin. The first resin is a resin having a higher crystallinity than the second resin contained in the sheath. The crystallinity of the first resin is preferably 30% or more and 90% or less. When the crystallinity of the first resin is 30% or more, the monomer for forming the ion exchange resin is less likely to be impregnated, and an ion exchange membrane with high mechanical strength is obtained. On the other hand, when the crystallinity of the first resin is too high, the interfacial adhesion between the core and the sheath may decrease. The crystallinity of the first resin is more preferably 50% or more and 80% or less.
[0019] The crystallinity of the first resin can be measured by differential scanning calorimetry (DSC). That is, first, the heat of fusion A1 of the first resin is measured. The heat of fusion A1 is divided by the heat of fusion B1 of polyethylene with a crystallinity of 100%, and the percentage of the value (A1 / B1) obtained is taken as the crystallinity of the first resin. The heat of fusion B1 of polyethylene with a crystallinity of 100% is 286.7 J / g. The crystallinity of the second resin can be obtained in a similar manner. That is, the heat of fusion A2 of the second resin obtained by DSC is divided by the heat of fusion B1 of polyethylene with a crystallinity of 100%, and the percentage of the value (A2 / B1) obtained is taken as the crystallinity of the second resin.
[0020] The sheath includes a second resin. The sheath may be composed of only the second resin. The second resin is a resin having a lower degree of crystallinity than the first resin contained in the core. The second resin may be the same type of resin as the first resin, or may be a different type of resin. The crystallinity of the second resin is preferably less than 30%. When the crystallinity of the second resin is less than 30%, the second resin is easily complexed with the ion exchange resin, and an ion exchange resin having excellent adhesion can be obtained. The crystallinity of the second resin is more preferably 15% or less.
[0021] The value obtained by subtracting the crystallinity of the second resin from the crystallinity of the first resin is preferably 1 or more and 80 or less, and more preferably 30 or more and 70 or less.
[0022] The first and second resins are preferably polyolefin resins. When the first resin is a high density polyethylene (HDPE) resin, the second resin is preferably at least one selected from the group consisting of a linear low density polyethylene (LLDPE) resin, a low density polyethylene (LDPE) resin, and an ethylene copolymer resin, and is more preferably an ethylene copolymer resin. When the first resin is a linear low density polyethylene resin, the second resin is preferably at least one of a low density polyethylene resin and an ethylene copolymer resin.
[0023] The ethylene copolymer resin may be a resin having a lower degree of crystallinity than the linear low-density polyethylene resin and the low-density polyethylene resin. The ethylene copolymer resin may be a random copolymer or a block copolymer. The ethylene copolymer resin is preferably a copolymer having an ethylene unit having ethylene as a repeating unit and a cyclic olefin unit having a cyclic olefin as a repeating unit, and is preferably a random copolymer thereof.
[0024] The ethylene copolymer resin preferably has a structure represented by the following formula (I).
[0025] [ka]
[0026] In formula (I), R 1 and R 2 are each a hydrogen atom, a halogen atom, or an alkyl group having 1 to 4 carbon atoms. 1 and R 2 may be bonded to each other to form a cycloalkyl group or a cycloalkene group. x and y represent the number of moles of ethylene units and cyclic olefin units, respectively. x:y=5-95:95-5 may be satisfied, or 30-70:70-30 may be satisfied.
[0027] The melt mass flow rate of the first resin measured under conditions of a temperature of 190° C. and a load of 2.16 kg in accordance with Japanese Industrial Standard K6922-2 is, for example, 0.1 g / 10 min or more and 30 g / 10 min or less, and preferably 0.5 g / 10 min or more and 15 g / 10 min or less.
[0028] The melt mass flow rate of the second resin measured under conditions of a temperature of 190° C. and a load of 2.16 kg in accordance with Japanese Industrial Standard K6922-2 is, for example, 0.1 g / 10 min or more and 30 g / 10 min or less, and preferably 0.5 g / 10 min or more and 15 g / 10 min or less.
[0029] The thickness of the core-sheath fiber is, for example, 10 decitex or more and 300 decitex or less, and more preferably 30 decitex or more and 150 decitex or less.
[0030] In a cross section perpendicular to the stretching direction of the sheath-core fiber, the ratio L3 / L2 of the cross-sectional area L3 of the sheath to the cross-sectional area L2 of the core is, for example, 0.05 to 4.3, and preferably 0.1 to 1.5. The cross-sectional area L3 of the sheath can be calculated by subtracting the cross-sectional area L2 of the core from the cross-sectional area L1 of the sheath-core fiber.
[0031] Core-sheath fibers can be produced by known methods, such as using two melt extruders to feed the core and sheath polymers into a core-sheath filament nozzle incorporating a core-sheath distributor to obtain a composite flow, which is then cooled and stretched.
[0032] The substrate typically does not include a resin that contains fluorine or chlorine atoms.
[0033] Examples of the cation exchange group of the ion exchange resin include a sulfonic acid group, a carboxylic acid group, a phosphonic acid group, a phenolic hydroxyl group, etc., and generally, the sulfonic acid group, which is a strongly acidic group, is preferred. Examples of the anion exchange group of the ion exchange resin include a quaternary ammonium group, a pyridinium group, a triazolium group, an imidazolium group, a primary amino group, a secondary amino group, a tertiary amino group, etc., and generally, the quaternary ammonium group or the quaternary pyridinium group, which is a strongly basic group, is preferred.
[0034] As the ion exchange resin, at least one of a hydrocarbon resin and a fluorine resin may be used. As the hydrocarbon resin, a styrene resin, an acrylic resin, or the like may be used. As the fluorine resin, a resin having a perfluorocarbon skeleton may be used. As the ion exchange resin, it is preferable to use a hydrocarbon resin, and it is more preferable to use a styrene resin. The styrene resin includes a styrene resin, a copolymer of a styrene derivative and a comonomer, and the like.
[0035] The ion exchange resin may contain a resin different from the resin that is the main component. Such a resin may be at least one selected from the group consisting of chlorine-based resins and hydrocarbon-based resins. From the viewpoint of increasing the adhesion between the substrate and the ion exchange resin, the resin is preferably one having a lower crystallinity than the first resin of the substrate, and more preferably the same type of resin as the second resin of the substrate. The proportion of these resins in the ion exchange resin is, for example, 1% by mass or more and 50% by mass or less. These other resins may be scattered in the form of particles or islands in the matrix of the ion exchange resin.
[0036] The ion exchange resin may further contain an additive such as a plasticizer. The plasticizer may be at least one selected from the group consisting of dibutyl phthalate, dioctyl phthalate, dibutyl phthalate, tributyl phosphate, and acetyl tributyl citrate. The proportion of these plasticizers in the ion exchange resin is, for example, 1% by mass or more and 20% by mass or less. The thickness of the ion exchange membrane is, for example, 20 μm or more and 400 μm or less.
[0037] Fig. 1 is a cross-sectional view showing an example of an ion exchange membrane according to an embodiment. The ion exchange membrane 10 shown in Fig. 1 includes a substrate 11 and an ion exchange resin 12 supported on the substrate 11. The substrate 11 is a plain weave fabric made of a core-sheath monofilament 1. The core-sheath monofilament 1 is made of a core portion 1a and a sheath portion 1b located around the core portion 1a.
[0038] The ion exchange membrane according to the embodiment is manufactured by, for example, a paste method. The method for producing an ion exchange membrane according to the embodiment includes, for example, filling a substrate with a polymerizable composition for forming an ion exchange resin to obtain a first composite membrane, polymerizing the first composite membrane to obtain a second composite membrane, and introducing an ion exchange group into the second composite membrane. Here, filling a substrate with a polymerizable composition means filling voids between fibers constituting the substrate with the polymerizable composition.
[0039] A method for producing an ion exchange membrane according to an embodiment may include filling a substrate with a polymerizable composition for forming an ion exchange resin to obtain a first composite membrane, stacking the first composite membrane and a release sheet and winding them into a roll to obtain a first wound body, polymerizing the first wound body to obtain a second composite membrane, peeling the release sheet from the second composite membrane, and introducing ion exchange groups into the second composite membrane.
[0040] As the release sheet, for example, a polyethylene terephthalate (PET) film, a polyvinyl alcohol film, a polycarbonate film, a polytetrafluoroethylene film, or the like is used.
[0041] The polymerization method for the first composite membrane may be thermal polymerization, photopolymerization, or a combination of these. From the viewpoint of obtaining an ion exchange membrane with excellent adhesion, thermal polymerization is preferred.
[0042] The thermal polymerization temperature of the first composite membrane is, for example, from 50° C. to 140° C., and preferably from 70° C. to 120° C. The thermal polymerization time is, for example, from 0.5 hours to 10 hours, and preferably from 1 hour to 6 hours, after the maximum temperature is reached.
[0043] The introduction of ion exchange groups is carried out, for example, by immersing the second composite membrane in a solution of a compound capable of introducing ion exchange groups. In one example, an anion exchange membrane having quaternary ammonium groups introduced therein is obtained by immersing the second composite membrane having chloromethylstyrene units in a trimethylamine solution for 12 hours or more. In another example, a cation exchange membrane having sulfonic acid groups introduced therein is obtained by contacting the second composite membrane having styrene units with concentrated sulfuric acid.
[0044] The polymerizable composition for forming the ion exchange resin contains a monomer capable of introducing an ion exchange group, and may further contain a crosslinking agent, a thickener, a polymerization initiator, and other additives.
[0045] The monomer capable of introducing an ion exchange group includes at least one selected from the group consisting of styrene, styrene derivatives, vinylpyridine, and vinylpyridine derivatives. The monomer capable of introducing an ion exchange group preferably includes at least one selected from the group consisting of styrene and styrene derivatives.
[0046] The styrene derivative may be at least one selected from the group consisting of chloromethylstyrene, vinyltoluene, vinylxylene, α-methylstyrene, vinylnaphthalene, and α-halogenated styrene.
[0047] The proportion of the monomer capable of introducing an ion-exchange group in the polymerizable composition is, for example, 10% by mass or more and 90% by mass or less, and preferably 30% by mass or more and 80% by mass or less.
[0048] The vinylpyridine derivative may be at least one selected from the group consisting of 4-vinylpyridine and 2-methyl-5-vinylpyridine.
[0049] As the crosslinking agent, a monomer having a polymerizable group with two or more functionalities is used. As the crosslinking agent, it is preferable to use at least one selected from the group consisting of divinylbenzene, divinylsulfone, butadiene, chloroprene, divinylbiphenyl, divinylnaphthalene, diallylamine, divinylpyridine, and trivinylbenzene, and it is preferable to use divinylbenzene.
[0050] The proportion of the crosslinking agent in the polymerizable composition is, for example, 30% by mass or less, and preferably 3% by mass or more and 20% by mass or less.
[0051] The thickener may be blended to increase the viscosity of the polymerizable composition, making it easier for the substrate to support the polymerizable composition, while increasing the adhesion between the ion exchange resin and the substrate. For example, fine resin particles are used as the thickener. The resin may be a resin having a lower crystallinity than the first or second resin contained in the woven fabric, which is the substrate, or may be the same type of resin as the second resin. The average particle size of the fine particles measured by the Coulter method is, for example, 0.1 μm or more and 20 μm or less.
[0052] The proportion of the thickener in the polymerizable composition is, for example, 1 mass % or more and 50 mass % or less, and preferably 3 mass % or more and 30 mass % or less.
[0053] The plasticizer may be at least one selected from the group consisting of dibutyl phthalate, bis(2-ethylhexyl) phthalate, and tributyl acetyl citrate. The proportion of the plasticizer in the polymerizable composition is, for example, 1% by mass or more and 20% by mass or less.
[0054] Examples of the polymerization initiator include benzoyl peroxide, p-chlorobenzoyl peroxide, decanoyl peroxide, lauroyl peroxide, acetyl peroxide, tert-butyl (2-ethylhexanoyl) peroxide hexanoate, and tert-butyl peroxyoctoate.
[0055] The proportion of the polymerization initiator in the polymerizable composition is, for example, 0.1% by mass or more and 15% by mass or less, and preferably 1% by mass or more and 10% by mass or less.
[0056] Other additives contained in the polymerizable composition include a polymerization inhibitor, a hydrochloric acid scavenger, and the like. EXAMPLES
[0057] Example 1 (Sheath-core fiber manufacturing) A core-sheath monofilament having a core made of linear low-density polyethylene LLDPE1 having a crystallinity of 34% and a sheath made of linear low-density polyethylene LLDPE2 having a crystallinity of 20% was obtained by the following method.
[0058] First, the polymer for the core and the polymer for the sheath were melted. As the polymer for the core, a linear low density polyethylene Novatec LL UF622 manufactured by Mitsui Chemicals was used. As the polymer for the sheath, a linear low density polyethylene Novatec LL UJ370 manufactured by Mitsui Chemicals was used. The molten polymers were pumped into a nozzle for a core-sheath monofilament incorporating a core and sheath distribution. In the nozzle, the core / sheath discharge ratio was 1 / 1.5. The spinning temperature was set to 290°C, and the composite polymer flow was discharged from the spinneret. After cooling the composite polymer flow, the speed was set to 19.2 m / min and the flow was wound around a roller heated to 60°C, and then the speed was set to 48 m / min and the flow was stretched 2.5 times between the roller heated to 60°C to obtain a stretched yarn of 620 dtex.
[0059] (Ion exchange membrane manufacturing) The core-sheath monofilament obtained by the above method was set on a small loom to obtain a plain weave fabric.
[0060] The plain weave fabric was filled with a polymerizable composition to obtain a first composite membrane. The first composite membrane was heated and polymerized at a temperature of 100°C for 3 hours to obtain a second composite membrane. The polymerizable composition used was a mixture of 83 parts by mass of styrene, 17 parts by mass of a 55% divinylbenzene solution, 23 parts by mass of low-density polyethylene resin powder, 5 parts by mass of dibutyl phthalate, and 3 parts by mass of benzoyl peroxide.
[0061] The second composite membrane was immersed in chlorosulfone at 40° C. for 2 hours to obtain a cation exchange membrane having sulfonic acid groups introduced therein.
[0062] Example 2 A core-sheath multifilament was obtained in the same manner as in Example 1, except that the polymer for the sheath was a low-density polyethylene Novatec LD LF342M1 manufactured by Mitsui Chemicals, the nozzle was a 12-hole nozzle for a core-sheath multifilament, the winding speed of the composite polymer flow around the roller was 12 m / min, and the speed during the stretching treatment was 30 m / min. The core was made of a linear low-density polyethylene LLDPE1 with a crystallinity of 34%, and the sheath was made of a low-density polyethylene LDPE1 with a crystallinity of 27%. The thickness of this filament was 680 dtex.
[0063] A cation exchange membrane was obtained in the same manner as in Example 1, except that the core-sheath multifilament obtained by the above method was used.
[0064] Comparative Example 1 A cation exchange membrane was obtained in the same manner as in Example 1, except that a multifilament of linear low density polyethylene LLDPE1 was used.
[0065] Comparative Example 2 A cation exchange membrane was obtained in the same manner as in Example 1, except that a multifilament of low-density polyethylene LDPE1 was used.
[0066] <Evaluation> (Adhesion) The surfaces of the ion exchange membranes obtained in the Examples and Comparative Examples were visually observed to check whether the resin had peeled off from the woven fabric. The evaluation criteria were as follows. The results are shown in Table 1.
[0067] 1: No peeling 2: Some of the resin has peeled off from the base material. 3: Most of the resin has peeled off from the substrate
[0068] [Table 1]
Claims
1. A core portion including a first resin; A substrate including a core-sheath fiber including a sheath portion that covers the periphery of the core portion and includes a second resin having a crystallinity lower than that of the first resin; an ion exchange resin supported on the substrate; An ion exchange membrane comprising:
2. The ion exchange membrane according to claim 1 , wherein the first resin has a degree of crystallinity of 30% or more and 90% or less.
3. The ion exchange membrane according to claim 1 , wherein the second resin has a crystallinity of less than 30%.
4. The ion exchange membrane according to claim 1 , wherein the first resin and the second resin are polyolefin-based resins.
5. 2. The ion exchange membrane according to claim 1, wherein the first resin is a high-density polyethylene resin, and the second resin is at least one selected from the group consisting of a linear low-density polyethylene resin, a low-density polyethylene resin, and an ethylene copolymer resin.
6. 2. The ion exchange membrane according to claim 1, wherein the first resin is a linear low-density polyethylene resin, and the second resin is at least one of a low-density polyethylene resin and an ethylene copolymer resin.
7. The ion exchange membrane of claim 1 , wherein the ion exchange resin comprises a styrene-based resin.
8. 2. An electrodialysis device comprising the ion exchange membrane of claim 1.
9. A diffusion dialysis device comprising the ion exchange membrane of claim 1.
10. A water electrolysis device comprising the ion exchange membrane according to claim 1.
11. A method for producing the ion exchange membrane according to claim 1, Filling the substrate with a polymerizable composition for forming the ion exchange resin to obtain a first composite membrane; polymerizing the first composite membrane to obtain a second composite membrane; introducing an ion exchange group into the second composite membrane to obtain an ion exchange membrane; A method for producing an ion exchange membrane comprising the steps of:
12. The method according to claim 11 , wherein the polymerizable composition contains particles of a resin having a lower crystallinity than the first resin.
Citation Information
Patent Citations
Cation-exchange membrane and manufacturing method therefor
JP2008231458A
Ion exchange membrane and method for producing ion exchange membrane with catalyst layer
WO2023038133A1